Collaborrative Approcahes to Building Digital Repositories in Africa - Bwamkuu, Africa J (Third International Conference on African Digital Libraries and Archives (ICADLA-3), 2016)
While there is exponential growth of local generated intellectual output from Africa, remains are challenges to make the local content visible and available at the global level. By 29th January, 2013, out of 2256 repositories listed in the Directory of Open Access Repositories (DOAR) at www.opendoar.org, only 60 repositories are in Africa, which is 2.66% of total repositories in DOAR. This statistics is consistent with many available studies which indicates that Africa’s’ contribution to the global knowledge is limited. The report released by Thomson Reuters on April 2010 also confirms that Africa's contribution to the global body of scientific research is very small and does little to benefit its own populations. With over 30 academic institutions that award bachelors, masters and PhD each year, Ethiopia faces the same challenges, make intellectual output accessible at the global level. Recognizing this fact, Ethiopian major actors in the educational field, in particular, the Consortium of Ethiopian Academic and Research Libraries (CEARL) and the National Education and Research Network of Ethiopia (EthERNet), have been actively exploring ways to address the challenge using the modern technology. CEARL, as content provider and EthERNet, as infrastructure operator, has been collaborating to unlock Ethiopian academic institutions’ knowledge using common digital repository. The collaboration is guided by Memorandum of Understanding (MoU) that harmonizes individual institutional policy framework. The paper explores the collaborative approaches whereby individual institutions pooled together resources and at the same time, jointly engage international partners specifically the International Network for the Availability of Scientific Publications (INASP), the Royal Tropical Institute (KIT), the African Digital Library Support Network (ADLSN) and the Institute of Development Studies (IDS) to bring about the national repository.
Keywords: Digital repository; Regional collaboration; Capacity building; Research output; Africa; Ethiopia